Increased CD163 expression is associated with acute-on-chronic hepatitis B liver failure - Ye, Hong (Baishideng Publishing Group Co., Limited, 2013)
AIM: To assess CD163 expression in plasma and peripheral blood and analyze its association with disease in acute-on-chronic hepatitis B liver failure (ACHBLF) patients. METHODS: A retrospective study was conducted from January 1, 2011 to January 1, 2012. Forty patients with ACHBLF (mean age 44.48 ± 12.28 years, range 18-69 years), 40 patients with chronic hepatitis B (CHB) (mean age 39.45 ± 12.22 years, range 21-57 years) and 20 age- and sex-matched healthy controls (mean age 38.35 ± 11.97 years, range 28-60 years) were included in this study. Flow cytometry was used to analyze the frequency of CD163+ peripheral blood mononuclear cells (PBMCs) and surface protein expression of CD163. Real-time transcription-polymerase chain reaction was performed to assess relative CD163 mRNA levels in PBMCs. Plasma soluble CD163 (sCD163) levels were measured by enzyme-linked immunosorbent assay. Clinical variables were also recorded. Comparisons between groups were analyzed by Kruskal-Wallis H test and Mann-Whitney U test. Statistical analyses were performed using SPSS 15.0 software and a P value < 0.05 was considered statistically significant. RESULTS: Flow cytometry showed that the population of CD163+ PBMCs was significantly greater in ACHBLF patients than in CHB patients and healthy controls (47.9645% ± 17.1542%, 32.0975% ± 11.0215% vs 17.9460% ± 6.3618%, P < 0.0001). However, there were no significant differences in mean fluorescence intensity of CD163+ PBMCs within the three groups (27.4975 ± 11.3731, 25.8140 ± 10.0649 vs 20.5050 ± 6.2437, P = 0.0514). CD163 mRNA expression in ACHBLF patients was significantly increased compared with CHB patients and healthy controls (1.41 × 10(-2) ± 2.18 × 10(-2), 5.10 × 10(-3) ± 3.61 × 10(-3) vs 37.0 × 10(-4) ± 3.55 × 10(-4), P = 0.02). Plasma sCD163 levels in patients with ACHBLF were significantly increased compared with CHB patients and healthy controls (4706.2175 ± 1681.1096 ng/mL, 1089.7160 ± 736.8395 ng/mL vs 435.9562 ± 440.8329 ng/mL, P < 0.0001). In ACHBLF patients, plasma sCD163 levels were significantly positively associated with model for end-stage liver disease scores (r = 0.5075, P = 0.008), hepatitis B virus-DNA (r = 0.6827, P < 0.0001), and negatively associated with prothrombin activity (r = -0.3348, P = 0.0347), but had no correlation with total bilirubin (r = 0.2551, P = 0.1122). Furthermore, sCD163 was obviously elevated in non-surviving patients compared with surviving patients with ACHBLF (5344.9080 ± 1589.5199 ng/mL vs 3641.7333 ± 1264.5228 ng/mL, P = 0.0321). CONCLUSION: CD163 and sCD163 may be related to disease severity and prognosis in ACHBLF patients.